Effects of Squeeze Pressure on Microstructure, Porosity and Hardness of an In-Situ Mg2Si/Al-Si-Cu Composite - Ozer, Gokhan; Guler, Kerern Altug; Lus, Huseyin Murat (CARL HANSER VERLAG, 2012)
The effect of applied pressure on microstructures and properties of an in-situ formed Mg2Si/Al-Si-Cu reinforced metal matrix composite fabricated by squeeze casting are investigated. Due to the wide solidification range and the high viscosity, this type of composites is prone ro shrinkage and gas porosity. In order to improve cast ability and to obtain better properties, the squeeze casting technique has been used. The results showed that primary Mg2Si crystals are formed by adding pure Mg into the hypereutectic Al-Si-Cu alloy (A380). It was found that, with the application of 30 MPa and 40 MPa pressure during solidification, the average size of primary Mg2Si particulates decreases from about 87 pm to about 21 and 18 pm and that the average porosity values of the cast samples is significantly decreased from 8.75 % to 0.50 and 0.35%, respectively.
Keywords: TENSILE PROPERTIES; EVOLUTION; Materials Science